Pengembangan Teknik Pengambilan Sampel Makrobenthos: Seleksi Alat dan Preparasi - Putro, S.P (JURNAL SAINS DAN MATEMATIKA, 2011)
Makrobenthic animals are invertebrates that relatively small (at least 500 Âµ ) and have short life spans, and play an important role as secondary producers in the structure of the food chain in the water ecosystem. They inhabit substrates/sediment at the bottom of the water column, either at the surface (epifauna) or in the sediment (infauna). Therefore, it needs proper method of collecting these animals. The procedures that need to be considered when collecting samples of macrofauna marine animals are sampling techniques, the type and size of the sampling tool , mesh size , and methods of preservation and fixation . In carrying out a study to determine the level of environmental disturbance aquatic ecosystems , in addition to disturbed areas , we need to use the control or reference areas for comparison . This area is ideally a region relatively undisturbed by human activity or environmental disturbance is assumed not to occur. Areas that are ecologically potentially disturbed areas can be cultivated fish / shrimp ponds in coastal systems , aquaculture floating net cage systems in a river or lake, disposal area (outlet) of industrial waste , etc. . While the reference area/control can be in the coastal mangrove areas , water areas without any human activities, and upstream river that are at least 1 km away from the disturbed area.